Legal Implications of Children Resulting from Free Sex "One Night Stand" in Indonesian Legal System - Nahdia Nazmi; Ahmad Mubarak; Laila Amalia; Najla Amali; Nazwatika Maulidhiya (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
The phenomenon of sexual relations without a marriage bond (one night stand) is increasing in urban communities, especially among teenagers and young adults, and has the potential to give birth to children out of wedlock who face legal problems related to the recognition of nasab, civil rights, and administrative status. This study aims to analyze the construction of legal protection for children born from these relationships in the Indonesian legal system. The method used is normative juridical research with a legislative and conceptual approach through literature studies. Legal sources analyzed include provisions in the Marriage Law, population administration law, criminal law, and important jurisprudence such as the Constitutional Court Decision No. 46/PUU-VIII/2010 which expands the civil relationship of children out of wedlock with their biological father based on scientific evidence and other valid evidence. The results of the study show that normatively the state has provided legal protection instruments for children out of wedlock, both through the recognition of civil relations and the guarantee of population administration rights. However, implementation in the field still faces obstacles in the form of social stigma, regulatory disharmony, as well as obstacles to proof and administrative procedures that are not fully child-friendly. It is concluded that legal protection of children born from non-marital relationships has undergone progressive development, but has not been optimal in practice. Therefore, this study recommends harmonizing regulations across sectors, simplifying administrative procedures for child recognition, and strengthening a non-discriminatory approach based on children's rights in law enforcement policies and practices.